2022
DOI: 10.1007/jhep08(2022)302
|View full text |Cite
|
Sign up to set email alerts
|

Speed of sound in cosmological phase transitions and effect on gravitational waves

Abstract: The energy budget for gravitational waves of a cosmological first order phase transitions depends on the speed of sound in the thermal plasma in both phases around the bubble wall. Working in the real-singlet augmented Standard Model, which admits a strong two-step electroweak phase transition, we compute higher order corrections to the pressure and sound speed. We compare our result to lower-order approximations to the sound speed and the energy budget and investigate the impact on the gravitational wave sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…For phase transitions that are dominated by the particle content of the Standard Model, one expects the speed of sound to remain rather close to c s,b ≈ 1/ √ 3 [51,52], and, depending on the required level of accuracy, computations in the bag model might suffice. For phase transitions taking place in a hidden sector, on the other hand, deviations from c s,b = 1/ √ 3 can be significant [51]. Especially in phase transitions in a strongly coupled sector, the sound speed can be very suppressed [31,53].…”
Section: Template Model and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For phase transitions that are dominated by the particle content of the Standard Model, one expects the speed of sound to remain rather close to c s,b ≈ 1/ √ 3 [51,52], and, depending on the required level of accuracy, computations in the bag model might suffice. For phase transitions taking place in a hidden sector, on the other hand, deviations from c s,b = 1/ √ 3 can be significant [51]. Especially in phase transitions in a strongly coupled sector, the sound speed can be very suppressed [31,53].…”
Section: Template Model and Resultsmentioning
confidence: 99%
“…It then becomes necessary to assume the sound speeds to be approximately temperature independent if we want to keep the discussion independent of the explicit expressions of the pressure and energy density. This approximation turns out to work very well in practice for typical models featuring a FOPT [48,49,51]. Inspection of Eqs.…”
Section: Model-independent Matching Equationsmentioning
confidence: 87%
“…It then becomes necessary to assume the sound speeds to be approximately temperature independent if we want to keep the discussion independent of the explicit expressions of the pressure and energy density. This approximation turns out to work very well in practice for typical models featuring a FOPT [60,61,63].…”
Section: Jcap07(2023)002mentioning
confidence: 85%
“…For phase transitions that are dominated by the particle content of the Standard Model, one expects the speed of sound to remain rather close to c s,b ≈ 1/ √ 3 [63,64], and, depending on the required level of accuracy, computations in the bag model might suffice. For phase transitions taking place in a hidden sector, on the other hand, deviations from c s,b = 1/ √ 3 can be significant [63]. Especially in phase transitions in a strongly coupled sector, the sound speed can be very suppressed [43,65].…”
Section: Template Model and Resultsmentioning
confidence: 99%
“…The authors of ref [59]. found that a slightly smaller speed of sound is expected in the broken phase of minimal DS models, which can lead to a sizeable suppression of the GW signal for detonations.…”
mentioning
confidence: 99%